Application of Fuzzy Controllers (Mamdani Model) for Liquid Flow Control Process in Chemical Industries - G. Vasanti; T.Viswanadham; A. Udaysree; B. Divya; K. Lakshmi; R. Ramya (Utilitas Mathematica, 2025)
The chemical industry, accurate control of liquid flow is essential for ensuring process effectiveness, product quality, and safety. Managing nonlinearities, uncertainties, and dynamic changes in flow control systems can be difficult for traditional controllers like proportional-integral-derivative (PID). This study investigates the use of fuzzy logic controllers- more especially, the Mamdani model—to control liquid flow in chemical reactions. The Mamdani fuzzy logic controller efficiently handles system complexities and uncertainties by utilizing membership functions and language rules. The performance of the Mamdani fuzzy controller and traditional PID controllers under various flow circumstances is compared through a thorough simulation. According to the results, the fuzzy controller performs better in dynamic conditions in terms of stability and adaptability. The Mamdani model offers a reliable and effective means to address flow control issues in the chemical industry, enhancing automation and operational dependability.